2023
DOI: 10.3390/ijerph20020932
|View full text |Cite
|
Sign up to set email alerts
|

Household Dietary Diversity among the Ethnic Minority Groups in the Mekong Delta: Evidence for the Development of Public Health and Nutrition Policy in Vietnam

Abstract: Poor household dietary diversity has been linked to malnutrition in individuals, households, and cumulatively in populations. High rates of malnutrition among Khmer ethnic children aged five years and younger have been reported in Tri Ton district, Vietnam. This paper aims to further investigate household dietary diversity and associated factors among Khmer ethnic minority populations in Vietnam. A cross sectional study was conducted from October 2018 to April 2019 in Tri Ton District, An Giang Province. By em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Conversely, haemolysis or contamination from adventitious zinc in the environment could mask low serum values. Notably, we found that MNDs were generally more prevalent among older adolescents (16)(17)(18) years old), which may reflect increased demands for both micro-and macronutrients during growth spurts and sex maturation during puberty. 24,25 In addition, repeated blood loss during menstruation will deplete iron stores particularly for females with limited access to iron-rich foods, or who have low iron absorption, which leads to ID with or without anaemia.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Conversely, haemolysis or contamination from adventitious zinc in the environment could mask low serum values. Notably, we found that MNDs were generally more prevalent among older adolescents (16)(17)(18) years old), which may reflect increased demands for both micro-and macronutrients during growth spurts and sex maturation during puberty. 24,25 In addition, repeated blood loss during menstruation will deplete iron stores particularly for females with limited access to iron-rich foods, or who have low iron absorption, which leads to ID with or without anaemia.…”
Section: Discussionmentioning
confidence: 72%
“…Minority groups are much more likely to live in moderate or severe food insecurity, and have less access to health care services including vaccinations, as well as the improved sanitation and water supply found in urban regions. 16,18 Ethnic minorities consequently have a higher prevalence of parasitic infections and diarrhea, leading to increased risk of stunting in early childhood (under 5 years of age). 19 Therefore, in the Vietnam Nutrition Strategy 2021-2030, ethnic minorities were seen as a critical target population to be individually evaluated for most nutrition targets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding was somewhat expected as children from poor households may have families who do not have latrines and do open defecation, and may not have access to foods high in iron, vitamin B12, and folic acid, given that poverty is usually linked to food insecurity, leading to increases the risk of developing anaemia. On the other hand, increased wealth increases food availability, access, and diversity in households, lowering the risk of anaemia in children [ 84 ]. The connections between household wealth and anaemia identified in this study further imply that socioeconomic factors directly influence children's haemoglobin levels.…”
Section: Discussionmentioning
confidence: 99%